2006
DOI: 10.1007/s11598-006-9016-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Approaches Revealing Prehistoric, Historic, or Recent Translocations and Introductions of Hares (Genus Lepus) by Humans

Abstract: Although only of medium size, and thus of little nutritional value compared to big game such as mammoths and ungulates, hares (Lepus spp.) probably have always been a food source for humans, as documented in archaeological finds. Nowadays, hares, particularly such species as the brown hare (L. europaeus), are among the most important game species in many European countries. For hunting, perhaps religious reasons, and in connection with certain myths, hares have been and are still being intentionally translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…This phylogeographic pattern is congruent with the hypothesis that all hares reported by Kasapidis et al (2005) carrying an A-haplotype are descendents of hares that have either immigrated naturally to SE mainland Europe and to those islands off the Anatolian coast via natural land bridges during the Last Glacial Maximum (LGM) or the early Holocene, or that have been transferred to those places in prehistoric or historic times by humans. Anthropogenic translocations have particularly been inferred for hares from Cyprus and Rhodes, as those latter islands were not connected by land bridges with mainland Anatolia during the Pleistocene, the major evolutionary epoch of the genus Lepus (Kasapidis et al 2005; see also Suchentrunk et al 2006;Masseti and De Marinis 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phylogeographic pattern is congruent with the hypothesis that all hares reported by Kasapidis et al (2005) carrying an A-haplotype are descendents of hares that have either immigrated naturally to SE mainland Europe and to those islands off the Anatolian coast via natural land bridges during the Last Glacial Maximum (LGM) or the early Holocene, or that have been transferred to those places in prehistoric or historic times by humans. Anthropogenic translocations have particularly been inferred for hares from Cyprus and Rhodes, as those latter islands were not connected by land bridges with mainland Anatolia during the Pleistocene, the major evolutionary epoch of the genus Lepus (Kasapidis et al 2005; see also Suchentrunk et al 2006;Masseti and De Marinis 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Other islands, such as Cyprus, where A-haplotypes have also been identified, had never been connected to mainland Anatolia during the late Pliocene/Pleistocene/Holocene, the period of evolution of the genus Lepus (e.g., Lopez-Martinez 2008). Thus, hares from those islands are hypothesized to be descendents of hares that have been transferred from Anatolian source populations to the islands by humans in prehistoric or historic times (Kasapidis et al 2005; see also Suchentrunk et al 2006). They might, however, also originate from other regions of the Middle East (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Despite the mutual geological history of Sardinia and Corsica, and their frequent connections during glacial times (Vigne, 1992), Sardinian hares have never occurred in Corsica, where Lepus corsicanus and L. europaeus are present instead (e.g., Mitchell-Jones et al, 1999;Suchentrunk et al, 2006b).…”
mentioning
confidence: 99%
“…No data were however collected from Corsica in this work. Some studies have later identified L. corsicanus as the sole species present in Corsica, but were essentially focused in limited areas of the island (Scalera and Angelici 2003;Riga et al 2003;Suchentrunk et al 2006). Pierpaoli and Randi (2005) have also identified this species in specimens collected in Corsica between 1999 and 2001, but no details on the location or the number of specimens studied were provided.…”
Section: Introductionmentioning
confidence: 99%